2009
DOI: 10.3102/0034654308325898
|View full text |Cite
|
Sign up to set email alerts
|

The Key to Global Understanding: World Languages Education—Why Schools Need to Adapt

Abstract: This review article is a plea for the education community to reconsider the place of world languages teaching within the schools. With globalization, languages education should be one of the strategic goals of public as well as private education. The article reviews research on the best age level for learning a language, the assets of bilingualism, the problems that arise from lack of recognition for other languages and cultures, the ways to change current language education, and the integration of internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 77 publications
0
37
0
2
Order By: Relevance
“…During the last decade, a lot of research focuses on the inseparable nature and relationship between culture and language (such as Byram, 1997;Kramsch, 2001;Pulverness, 2003;McKay, 2003) which reflects that language learning grounded in culture may guide the learners to develop a sense of multiculturalism and they may have an improved sense of achievement in learning a foreign language (Byrnes, 2008;Rubio, 2007;Tochon, 2009). …”
Section: Relevant Studiesmentioning
confidence: 99%
“…During the last decade, a lot of research focuses on the inseparable nature and relationship between culture and language (such as Byram, 1997;Kramsch, 2001;Pulverness, 2003;McKay, 2003) which reflects that language learning grounded in culture may guide the learners to develop a sense of multiculturalism and they may have an improved sense of achievement in learning a foreign language (Byrnes, 2008;Rubio, 2007;Tochon, 2009). …”
Section: Relevant Studiesmentioning
confidence: 99%
“…Rhodes and Pufahl warn that while US high school foreign language programs have remained stable in the last decade, foreign language programs at the elementary and middle school levels have 'decreased substantially ' (2009, 7). Such findings are particularly troubling in light of the numerous benefits of a bilingual/multilingual education (Tochon 2009). …”
Section: Discussion: Policy Recommendations For Increasing Global Commentioning
confidence: 96%
“…Indeed, in their survey of 1,835 public elementary schools, Pufahl and Rhodes (2011) found that only 15% taught world language in 2008, a figure that represented a significant decline from a previous survey they had conducted in 1997, while 91% of high schools surveyed offered world language instruction (p. 261). This contrasts with the known benefits of starting world language education earlier in children's educational trajectory, as is done in many other countries (Pufahl et al, 2001;Tochon, 2009). In 1999, the Educational Testing Service Policy Information Center reported that, based on a national sample of students who graduated from high school in 1994, 74% of high schools represented in the study did not require any world language course work for graduation (Finn, 1999, n.p.).…”
Section: Introductionmentioning
confidence: 89%